The global effects of the euro debt crisis - Livio Stracca (European Central Bank (ECB), 2013)
This paper is an event study focusing on the global effects of the euro debt crisis in 2010-2013. After identifying 18 key exogenous crisis events, I analyse the impact on equity returns, exchange rates and government bond yields in 12 advanced and 13 emerging countries. The main effect of euro debt crisis events is a rise in global risk aversion accompanied by fall in equity returns, in particular in the …financial sector, in advanced countries (but not in emerging countries). The effect on bond yields is not statistically significant for the whole set of countries, but is significant and negative for key advanced countries such as the US and the UK. The paper also analyse the transmission channels by looking at how pre-crisis country characteristics influence the strength and direction of the spill-over, concluding that the transmission hinges more on trade than on fi…nance.
Keywords: F3; 330; Contagion; Euro debt crisis; global risk aversion; spill-over